Fenomena Fear of Missing Out (FoMO) pada Perilaku Konsumtif Generasi Z di Media Sosial Instagram Mahasiswa Universitas Muhammadiyah Buton - Zahra Qoniah; Muh. Rizal Ardiansah Putra; Hastuti Hastuti (Yayasan Literasi Sains Indonesia, 2026)
The phenomenon of Fear of Missing Out (FoMO) has increasingly become a behavioral pattern among Generation Z along with the rapid growth of social media usage. This study aims to analyze the influence of FoMO on consumptive behavior related to digital shopping activities on Instagram among university students. The research applied a qualitative method with a phenomenological approach. Participants were selected using a snowball sampling technique based on their Instagram usage intensity and online purchasing experience. Data were collected through in-depth interviews, digital observation, and documentation, then analyzed using data reduction, data display, and conclusion verification. The findings indicate that FoMO emerges through a combination of algorithmic exposure, such as Instagram Stories, Reels, personalized advertisements, and continuous social comparison with influencers and peers. These triggers encourage impulsive purchasing behavior driven by the need for social validation, self-presentation, and alignment with online trends rather than functional needs. Most participants admitted purchasing products to maintain digital presence and enhance online identity. In conclusion, FoMO significantly shapes students’ consumption behavior and highlights that digital consumption is increasingly connected to identity construction, social validation, and perceived status within the social media environment.